Heritage in the Context of Globalization - Biehl, Peter F. author. aut Link
X, 125 p. 5 illus.
Keywords: This brief is the proceedings of two roundtables and forums organized by Eszter Bánffy, Peter Biehl, Douglas Comer, and Christopher Prescott and sponsored by the European Association of Archaeologists (EAA) and the Society for American Archaeology (SAA) held at the 76th SAA annual conference in Sacramento in April 2011, and the 17th EAA annual conference in Oslo in September 2011. The book is organized around five main issues with the goal to stimulate discussion, research and practices within the field: Traditions and legal regulations of heritage and its management The teaching of cultural heritage; public outreach and university training Heritage and national identity The future of cultural heritage in a globalized and digitized world This book is thus be an exploration of the various experiences in Europe and the Americas to better understand, in the vast field of archaeology and cultural heritage management, where we are today, where we might be, and where we hope to be in the near future. .